Market failure or success : the new debate - Crampton, Eric.; Cowen, Tyler; The Independent Institute (Cheltenham, UK ; Northampton, Mass., USA : E. Elgar, 2002)
Recent years have seen the development of new theories of market failure based on asymmetric information and network effects. According to the new paradigm, we can expect substantial failure in the markets for labor, credit, insurance, software, new technologies and even used cars, to give but a few examples. This volume brings together the key papers on the subject, including classic papers by Joseph Stiglitz, George Akerlof and Paul David.
"A book from the Independent Institute."
Includes bibliographical references and index.
oif 30/07/14; 20/02/15
Loan
Keywords: Economic policy; Business cycles; Information theory in economics; Capitalism; Welfare economics; Central planning; Economics -- History -- 20th century